2013
DOI: 10.1016/j.abb.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectroscopic evaluation of skin carotenoids as a biomarker of carotenoid status for human studies

Abstract: Resonance Raman Spectroscopy (RRS) is a non-invasive method that has been developed to assess carotenoid status in human tissues including human skin in vivo. Skin carotenoid status has been suggested as a promising biomarker for human studies. This manuscript describes research done relevant to the development of this biomarker, including its reproducibility, validity, feasibility for use in field settings, and factors that affect the biomarker such as diet, smoking, and adiposity. Recent studies have evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 71 publications
(117 reference statements)
4
87
1
1
Order By: Relevance
“…This may be explained by several factors that influence carotenoid status in addition to diet. We investigated potential determinants of observed skin carotenoid concentrations and discussed the existing literature in a recent review (19). Briefly, we found that season can affect skin carotenoid status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by several factors that influence carotenoid status in addition to diet. We investigated potential determinants of observed skin carotenoid concentrations and discussed the existing literature in a recent review (19). Briefly, we found that season can affect skin carotenoid status.…”
Section: Discussionmentioning
confidence: 99%
“…The blood carotenoid concentration is considered to be the best biological marker of V/F intake (18) but is invasive and expensive. Skin carotenoid status assessed by resonance Raman spectroscopy (RRS) has emerged as a promising new biomarker of V/F intake in both children and adults and was recently reviewed by Mayne et al (19). We have shown a wide distribution of skin carotenoid concentrations (20)(21)(22), high reproducibility over 6 mo in the absence of intervention (21,23), and validity compared with blood concentrations (21,24), skin biopsy (21,25), and reported V/F intake (20,21)-all necessary characteristics for a biomarker of nutritional status and food intake.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] A novel non-invasive RRS has recently been developed to measure the level of skin carotenoids. [7][8][9][10] This has been validated as a biomarker of the carotenoid status and a reliable probe of the redox balance of healthy humans, 9 and applied in dietetic studies to monitor body's antioxidant status to eventually suggest dietary interventions. 28 In this work for the first time the level of dermal carotenoids, measured by Raman spectroscopy and expressed as SCS, has been assessed in patients with a transfusion-dependent thalassemia, and the use of this methodologic approach has been even in this pathology characterized by a remarkable individual oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Intracardiac and liver iron, and liver fibrosis, have been monitored in transfusiondependent thalassemia patients by magnetic resonance imaging based T2* multislice measurements, 6 and by hepatic transient elastography (FibroScan Âź ) examinations. These measurements have been matched with a non-invasive, and yet unexplored in clinical practice, evaluation of body's oxidative stress through measurement of antioxidant carotenoids in skin, [7][8][9][10] by a spectroscopic method based on Raman technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation